2015
DOI: 10.1007/s10534-015-9851-y
|View full text |Cite
|
Sign up to set email alerts
|

Impedance technology reveals correlations between cytotoxicity and lipophilicity of mono and bimetallic phosphine complexes

Abstract: Label free impedance technology enables the monitoring of cell response patterns posttreatment with drugs or other chemicals. Using this technology, a correlation between the lipophilicity of metal complexes and the degree of cytotoxicity was observed. Au(L1)Cl (1), AuPd(L1)(SC 4 H 8 )Cl 3 (1a) and Au(L2)Cl (2) (L1 = (diphenylphosphino-2-pyridine); L2 = 2-(2-(diphenylphosphino)ethyl)-pyridine) were synthesised, in silico drug-likeness and structure activity relationship (SAR) monitored using impedance technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Consequently, drug lipophilicity affects its activity, toxicity to healthy tissues and is directly related to plasma protein binding and metabolism of the drug [37]. Changes in drug lipophilicity by incorporating the suitable functional groups in the molecule have shown great impact in anticancer activity and host toxicity [38,39].…”
Section: Preparation Of [Au(c≡c-2-nc 5 H 4 )(Pta)]mentioning
confidence: 99%
“…Consequently, drug lipophilicity affects its activity, toxicity to healthy tissues and is directly related to plasma protein binding and metabolism of the drug [37]. Changes in drug lipophilicity by incorporating the suitable functional groups in the molecule have shown great impact in anticancer activity and host toxicity [38,39].…”
Section: Preparation Of [Au(c≡c-2-nc 5 H 4 )(Pta)]mentioning
confidence: 99%
“…To comprehensively analyze the hepatotoxicity induced by azithromycin impurities and further verify the results drawn by the assessment model, we investigated the liver toxicity of azithromycin impurities in vivo and in vitro . First, the ADMET properties of these impurities are predicted in Table 3 , the values of topological polar surface area (TPSA) and log P showed that azithromycin impurities presented high lipophilicity, indicating these impurities might have good membrane permeability or oral absorption ( Fonteh et al, 2015 ; Qidwai, 2016 ). Among them, impurity H has the highest TPSA and log P values.…”
Section: Resultsmentioning
confidence: 99%
“…The PSA_2D of impurities C and F were all less than 100 indicating that two compounds had good oral absorption or membrane permeability (Qidwai, 2016). CAZ and impurities A, B, C, E, F, G, and H were predicted as having ideal lipophilicity (AlogP98 ≤ 5), impurity D and I were shown as poor lipophilicity (AlogP98 > 5) (Fonteh et al, 2015). The result suggested that impurity D and I have poor absorption and permeation.…”
Section: Resultsmentioning
confidence: 99%